THE PRACTICE OF GROUP THERAPY FOR HIGH-RISK PRISONERS AS AN EFFORT TO BUILD SELF-ADJUSTMENT - Rahman, Anthony Putra Aditya; Equatora, Muhammad Ali (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to explore the practice of group therapy for high-risk prisoners in building self-adjustment at the Banjarmasin Class IIA Correctional Institution. The method used was a case study, where data was obtained through observation and interviews with prisoners and prison officers. The results showed that group therapy is effective in helping prisoners overcome internal conflicts, increase social support, and strengthen relationships between prisoners. The active participation of prisoners in therapy sessions is an important indicator in their adjustment process. In addition, a conducive prison environment and support from officers also contributed to the success of the therapy. In conclusion, the practice of group therapy not only supports prisoners' self-adjustment but also encourages the development of positive social relationships, making it important to be implemented sustainably in rehabilitation programs in correctional institutions. Keywords: Therapeutic Practice; Prisoners; Self Adjusment